Impaired Fertility Associated with Subclinical Hypothyroidism and Thyroid Autoimmunity: The Danish General Suburban Population Study - Anne-Dorthe Feldthusen; Palle L. Pedersen; Jacob Larsen; Tina Toft Kristensen; Christina Ellervik; Jan Kvetny (Journal of Pregnancy, 2015)
Introduction. The aim of this study was to estimate the significance of TSH, thyroid peroxidase antibody (TPOAb), and mild (subclinical) hypothyroidism in women from The Danish General Suburban Population Study (GESUS) on the number of children born, the number of pregnancies, and the number of spontaneous abortions. Methods. Retrospective cross sectional study of 11254 women participating in GESUS. Data included biochemical measurements and a self-administrated questionnaire. Results. 6.7% had mild (subclinical) hypothyroidism and 9.4% prevalent hypothyroidism. In women with mild hypothyroidism TPOAb was significantly elevated and age at first child was older compared to controls. TSH and TPOAb were negatively linearly associated with the number of children born and the number of pregnancies in the full cohort in age-adjusted and multiadjusted models. TSH or TPOAb was not associated with spontaneous abortions. Mild (subclinical) hypothyroidism was associated with a risk of not having children and a risk of not getting pregnant in age-adjusted and multiadjusted models. Prevalent hypothyroidism was not associated with the number of children born, the number of pregnancies, or spontaneous abortions. Conclusion. Impaired fertility is associated with TSH, TPOAb, and mild (subclinical) hypothyroidism in a Danish population of women.